The Dual Process model: the effect of cognitive load on the ascription of intentionality - Zucchelli, Micaela Maria; Matteucci Armandi Avogli Trotti, Nicola; Pavan, Andrea; Piccardi, Laura; Nori, Raffaella (Frontiers in Psychology, 2025)
BackgroundThe classic Dual Process model posits that decision-making is determined by the interplay of an intuitive System 1 and a logical System 2. In contrast, the revised model suggests that intuition can also be logical. The Cognitive load paradigm has been used to distinguish underlying rational and intuitive processes, as it tends to lead to the use of heuristics over reasoning. Through two studies, we aimed to investigate the impact of two increasing levels of extraneous cognitive load on intentionality decision-making by comparing the two decision-making models.MethodsThe task required participants to attribute intentionality to negative and positive side effects, which were foreseeable but not deliberately intended. This compared an intuitive response, focused on the outcome, with a logical one, focused on the absence of intention. Participants were randomly assigned to one of the six experimental conditions, each with varying cognitive loads (high cognitive load vs. low cognitive load vs. no cognitive load) and scenario valence (negative vs. positive). In Study 1, cognitive load was made by introducing a concurrent task during intentionality attribution, whereas in Study 2, cognitive load was accomplished by associating the dual-task with a time pressure paradigm. Participants under cognitive load were expected to exhibit cognitive resource exhaustion, providing greater judgments of intentionality for negative outcomes and lower for positive ones, due to the dominance of intuition, compared to evaluations provided by participants who were not under cognitive load.ResultsIn both studies, cognitive load reduced intentionality attributions for positive side effects compared to the no-load condition, with response times being longer for positive side effects than for negative ones.ConclusionThis pattern suggests System 2 intervention for positive outcomes and System 1 dominance for negative ones. Therefore, introducing cognitive load enabled us to identify the different roles of the two decision systems in intentionality attribution.